Programming Microsoft Dynamics 365 Business Central : Build Customized Business Applications with the Latest Tools in Dynamics 365 Business Central, 6th Edition. - Brummel, Mark (Packt Publishing, Limited, 2019)
Programming Microsoft Dynamics 365 Business Central will help you effectively use the development tools that are built into Dynamics Business Central. You will understand the strengths of Microsoft Dynamics 365 Business Central's development tools and how they can be applied to address functional business requirements.